UJI DAYA ADAPTASI BEBERAPA VARIETAS BAWANG PUTIH (Allium sativum L.) DI KABUPATEN PESISIR SELATAN - Obel Obel; Elara Resigia; Jamsari Jamsari (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2020)
Garlic (Allium sativum L.) is one of the important commodities in the horticultural sub-sector which is one of the basic needs of the community that must be fulfilled. However, garlic production in Indonesia has not been able to meet the demands of society's needs. For this reason, an additional area of land for garlic development is aimed at the optimal suitability of environmental physical factors. The use of superior varieties is one of the technologies that play a role in increasing the productivity of garlic. This research was conducted in May - August 2020 in Tarusan and Muaro Aie Bayang Utara, Pesisir Selatan Regency, West Sumatra Province with a randomized block design using Lumbu Hijau, Lumbu Kuning and local varieties of Bukik Sileh Solok as treatment. The results showed that the varieties of Lumbu Kuning and Lumbu Hijau were able to adapt well in Muaro Aie with an altitude of 322 masl compared to Tarusan with an altitude of 4 masl. Both varieties gave a fairly good growth response and yield, although only half of the description of these varieties.